2004
DOI: 10.1055/s-2004-860897
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Apnea Avoidance Pillow Effects on Obstructive Sleep Apnea Syndrome and Snoring

Abstract: A uniquely designed pillow (SONA Pillow) is effective in reducing the number of events in patients with mild to moderate obstructive sleep apnea. Using this pillow also reduces snoring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(10 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…A statistically significant decrease in snoring was reported by Zuberi et al [42] in 22 patients with POSA treated with PT (triangular pillow), whilst Wenzel et al [43] reported a decrease in snoring rate from 15.4 % to 9.8 % in 14 patients with POSA treated with PT (vest). Loord and Hultcrantz [44] reported that half of the patients ( n  = 18) treated with PT (soft vest attached to a board with pillow) snored more frequently; specifically, six snored less frequently, nine snored more frequently, and for two, there was no difference.…”
Section: Positional Therapymentioning
confidence: 89%
“…A statistically significant decrease in snoring was reported by Zuberi et al [42] in 22 patients with POSA treated with PT (triangular pillow), whilst Wenzel et al [43] reported a decrease in snoring rate from 15.4 % to 9.8 % in 14 patients with POSA treated with PT (vest). Loord and Hultcrantz [44] reported that half of the patients ( n  = 18) treated with PT (soft vest attached to a board with pillow) snored more frequently; specifically, six snored less frequently, nine snored more frequently, and for two, there was no difference.…”
Section: Positional Therapymentioning
confidence: 89%
“…They found a significance decrease in snoring rate from 36.7 to 15.7%. Zuberi et al also reported a significant reduction in snoring in patients with POSA treated with a triangular pillow [33]. In a study by Wenzel et al, patients with POSA were treated with a vest preventing the supine position [34].…”
Section: Discussionmentioning
confidence: 99%
“…The study investigating the polysomnographic effects of a commercially available pillow published by Zuberi et al [3] comes to some conclusions about its beneficial effect on sleepdisordered breathing, which I believe are not substantiated by the fashion in which the data was presented.…”
Section: Dear Editorsmentioning
confidence: 95%